Pengembangan Buku Pengayaan Jenis Invertebrata di Pantai PandaratanTapanuli Tengah Berbasis Kontekstual untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA: Development of a Contextual Enrichment Book Based on Invertebrate Diversity at Pandaratan Beach, Central Tapanuli to Improve Grade 10 Senior High School Students’ Learning Outcomes - Marina Azzahra Nasution; Khairiza Lubis; Ashar Hasairin; Ely Djulia (Madrasah Tsanawiyah DDI Cilellang, 2026)
Utilizing local potential as a learning resource can create more contextual and meaningful learning. This study aims to develop a non-textbook on invertebrate Animalia diversity in Pandaratan Beach, Central Tapanuli based on contextual validity that is valid, practical, and effective in improving students' cognitive learning outcomes. The research method used is Research and Development (R&D) with the Four-D (4-D) model which includes define, design, develop, and disseminate. The research subjects consisted of expert validators, biology teachers, and grade X students of SMA Negeri 1 Tukka. Data were collected through validation sheets, response questionnaires, and cognitive learning outcome tests. The results showed that there were 31 invertebrate Animalia species used as the basis for developing non-textbooks. The validation results showed very high feasibility from material experts (95.3%), learning design experts (94.01%), and graphic design experts (84.51%). The teacher's response obtained 99.47% with a very good category, and the student's response was also very good. The effectiveness test showed an N-Gain value of 0.71 (high category), while the t-test obtained a significance of 0.000 (p < 0.05). This indicates that the use of contextual-based non-textbooks has a significant effect on improving students' cognitive learning outcomes. Thus, the developed product is declared valid, practical, and effective as a learning resource for Animalia.